The internationalization of development policy - Joachim Betz (Intereconomics, 1979)
It has been evident for some time that the proportion of the public development aid which is distributed through multilateral channels is increasing. The causes of this process are examined in the following article which is based on the author's doctor thesis.
Keywords: 330; Development Assistance